2015
DOI: 10.1007/s12928-015-0372-y
|View full text |Cite
|
Sign up to set email alerts
|

Subclinical very late thrombus formation inside and outside the everolimus-eluting stent implanted 3 years prior in a patient with provoked coronary spasms

Abstract: A 63-year-old man with non-ST-elevation acute myocardial infarction had undergone PROMUS Element stent implantation for stenosis with thrombus in the left main trunk and the proximal left anterior descending artery. A 6-month follow-up angiography revealed no restenosis or stent thrombosis, but severe provoked spasms in three vessels, for which medications were administered. Three years later, the patient experienced new-onset rest angina one morning. Optical coherence tomography revealed subclinical very late… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 22 publications
0
1
0
Order By: Relevance
“…At present, we often perform PCI with coronary stent implantation for significant organic coronary artery stenosis. Coronary spasm occurring after coronary stent implantation has become a clinical problem [25,[102][103][104][105][106][107]. A previous report showed that excessive coronary vasoconstriction of PCI-treated coronary arteries in response to intracoronary injection of ACh was more frequent in patients treated with bare metal stents (BMS) than in those treated only with balloon angioplasty, suggesting that endothelial dysfunction induced by PCI was involved in the progression of atherosclerosis [108].…”
Section: Ach-provoked Coronary Spasm and Organic Coronary Artery Stenmentioning
confidence: 99%
“…At present, we often perform PCI with coronary stent implantation for significant organic coronary artery stenosis. Coronary spasm occurring after coronary stent implantation has become a clinical problem [25,[102][103][104][105][106][107]. A previous report showed that excessive coronary vasoconstriction of PCI-treated coronary arteries in response to intracoronary injection of ACh was more frequent in patients treated with bare metal stents (BMS) than in those treated only with balloon angioplasty, suggesting that endothelial dysfunction induced by PCI was involved in the progression of atherosclerosis [108].…”
Section: Ach-provoked Coronary Spasm and Organic Coronary Artery Stenmentioning
confidence: 99%